There Is a God in Heaven Who Reveals Mysteries: Failed Divination and Divine Revelation in Daniel 2 and Genesis 41 - Melvin, David P. (2019)
This article examines accounts of dream interpretation in the Joseph story and the court tales of Daniel as theological critiques of divinatory methods that relied upon the skill and knowledge of the diviner, such as the various forms of deductive divination practiced in the royal courts of the ancient Near East. Building upon studies of dream/vision divination by Susan Niditch, Jean-Marie Husser, and A. Leo Oppenheim, it utilizes historical-critical and comparative/contextual methodologies to read Dan 2 and Gen 41 in light of dream divination as it was commonly practiced in the royal courts of the ancient Near East. It finds that, in both of these texts, as the protagonist successfully interprets a dream that his Egyptian or Babylonian counterparts cannot, the inability of human diviners to uncover divine secrets is highlighted, along with the explicit confession of the Israelite protagonist that he interprets not due to his superior intelligence or ability but by divine inspiration. This suggests that both Gen 41 and Dan 2 hold up dream interpretation that relies upon divine inspiration by the true God of heaven, rather than technical knowledge, as a method superior to divination. Finally, these texts provide evidence for the use of an apocalyptic-style revelation motif in literary contexts that suggests a wisdom setting and background, particularly in the Jewish diaspora, where they championed the Jewish God as the sole true revealer of mysteries.